Job Satisfaction as a Mediating Variable of Servant Leadership and Career Development on Gen Z Performance - Nur, Haris Sukandar; Handayani, Dewi Sri; Febriana, Artha (Universitas Dian Nuswantoro Semarang, 2022)
This study aims to determine the effect of service leadership, career development, and satisfaction on gen z who work in digital marketing or sales executives in Central Java. This study is a quantitative study. The population of this study was all gen z workers. The data collection method used interviews and questionnaires to 116 gen z who worked for at least one year in digital marketing or sales executives. Data analysis techniques with SEM PLS. The results of the study showed that our research on the impact of servant leadership and career development on Gen Z employee performance in Central Java, with employee satisfaction as a mediating factor, reveals the following: Employee satisfaction significantly and positively impacts performance. Career development significantly and positively impacts both performance and satisfaction. Servant leadership significantly and positively impacts both performance and employee satisfaction.